Research on novel var compensator based on dual-rotary phase-shifting transformers and its control strategy. (January 2023) - Yan, Xiangwu; Deng, Wanjun; Wang, Guanghua; Rasool, Aazim; Qi, Shaomeng
Highlights: A novel rotary var compensator topology circuit based on dual RPSTs is proposed. The NRVC compensation principle and capacity constraint is studied. A dual closed-loop control strategy of power and current is proposed. Simulation and experimental results demonstrate the effectiveness of the system. Abstract: With the continuous increase in the penetration of distributed power with random output, the acceleration of the urban cableization rate and the rapid development of supergrid, the active distribution network puts forward higher requirements for the performance of dynamic reactive power compensation. A topology of novel rotary VAR compensator (NRVC) is proposed by integrating the current source static synchronous compensator with the continuous regulation characteristics of dual rotary phase-shifting transformers. The NRVC compensation principle is analyzed by establishing the steady-state mathematical model of dual rotary phase-shifting transformers and NRVC. The dynamic response performance and universal applicability are improved by considering its compensation capacity constraints, applying the instantaneous reactive power theory, and constant power factor control. A dual closed-loop decoupling control strategy of power outer-loop and current inner-loop is also presented to prevent internal overcurrent. Finally, the simulation and experimental results are performed to verify the effectiveness of the proposed system and control strategy, which realized bidirectional and continuous regulation of compensated reactive power, and has manifold advantages: low cost, strong shock resistance, large heat capacity, simple control, and no harmonic pollution.